Carcinogenic risks of inorganic arsenic in white rice in Asia - Jiana Chen; Chuanming Zhou; Fangbo Cao; Min Huang (Journal of Agriculture and Food Research)
This study estimated the incremental lifetime cancer risk (ILCR) of inorganic arsenic (iAs) from white rice ingestion in eight countries (China, Korea, Pakistan, Saudi Arabia, Thailand, Vietnam, Bangladesh, and Cambodia) in Asia by using data collected from published literature (n = 4857). ILCR of iAs exposure from white rice ingestion substantially varied with region, ranging from 0.37 to 13.46 per 10000 people, with an average of 6.12 per 10000 people. Bangladesh had the highest ILCR, followed by Cambodia, Vietnam, Thailand, China, Korea, Saudi Arabia, and Pakistan. Carcinogenic risks of iAs exposure from white rice ingestion in China, Korea, Thailand, Vietnam, Bangladesh, and Cambodia are at an unacceptable level (more than 1 per 10000 people). Linear regression analysis indicated that ingestion rate and inorganic arsenic content were the critical factors determining regional differences in carcinogenic risk of iAs exposure from white rice ingestion in Asia.